Pemahaman mahasiswa pada mata pelajaran metode statistik moodle melalui pendekatan ilmiah - Puspananda, Dian Ratna; Sujiran, Sujiran; Azzahro, Isna Choirun Nisa’ (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2022)
This study aims to investigate the understanding of mathematics department students in the subject of statistical method at moodle through scientific approach. The research design is qualitative research. The research subjects are fourth semester students of mathematics department at IKIP PGRI Bojonegoro who are chosen using purposive sampling. The data is analysed using data triangulation. The results of study reveal that from all five subjects; in the online learning using moodle; get so easy in understanding the learning materials. The learning becomes flexible; it can be carried out anywhere and anytime. Students are able to study by looking for learning references from other sources. Hovewer, there are several problems in the online learning such as lecturer’s explanation is not as clear as when learning in class, there are more assignments given, and several materials have not been mastered by students. In the online learning, students have to be more focus when it is directed from YouTube. When the students have not understood the learning material in online learning, they can ask it to the lecturer or their classmates. Therefore, five subjects can anwer the questions about homogeneity and balance tests. Their completion steps are precise and perfect.